ICLASS 2021
DOI: 10.2218/iclass.2021.5834
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of a single ethanol droplet interacting with a premixed laminar CH4/air flame

Abstract: Among all phenomena occurring in liquid-fueled combustion chambers, one basic process is the interaction of droplets with the flame. Therefore, it is essential to understand the dynamics of an individual droplet interaction with a flame front in order to analyze more complex flames. The aim of this study is to investigate the evaporation of a single ethanol droplet interacting with a premixed laminar CH4/air flame. In the experimental part of the study, the droplet was injected into the stagnation flame. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The evaporation of an isolated ethanol droplet was investigated previously under premixed methane/air flame conditions, and it is found that 50 µm diameter is high enough to cross the flame front under elevated temperatures, regardless of the gas composition [30]. Hence, the droplet passage through the flame field and its effects on the flame structure can properly be observed under the fixed conditions, reported in Table 2.…”
Section: Local Extinction Due To Droplet Passage On Stagnation Flamementioning
confidence: 96%
See 1 more Smart Citation
“…The evaporation of an isolated ethanol droplet was investigated previously under premixed methane/air flame conditions, and it is found that 50 µm diameter is high enough to cross the flame front under elevated temperatures, regardless of the gas composition [30]. Hence, the droplet passage through the flame field and its effects on the flame structure can properly be observed under the fixed conditions, reported in Table 2.…”
Section: Local Extinction Due To Droplet Passage On Stagnation Flamementioning
confidence: 96%
“…The schematic of the stagnation burner is given in Figure 2 (a). Details of the stagnation flame burner can also be found in other studies [30], [26]. Experimental configuration is represented in Figure 2 (b).…”
Section: Ground Experiments: Stagnation Flamementioning
confidence: 99%